Photocatalytic Fuel Cells for Simultaneous Wastewater Treatment and Power Generation: Mechanisms, Challenges, and Future Prospects - Hari Bhakta Oli; Allison A. Kim; Mira Park; Deval Prasad Bhattarai; Bishweshwar Pant (Energies, 2022)
Technological advancement is accompanied by excessive consumption of fossil fuels and affluent uses of chemical substances in many sectors, including transportation and manufacturing companies, and so on. Being an exhaustible resource, the excessive use of fossil fuels and of chemical substances may lead to a serious energy crisis in the long run, and it may additionally impose environmental pollution. Attempts have been made in the solution of such serious issues from every nook and corner. Nonetheless, no method has been found to be a panacea in waste water treatment and subsequent beneficiaries. One of the attempts in the solution to such issues is the application of photocatalytic technology, which could serve as a dual function in environmental remediation and clean energy production. A photocatalytic fuel cell is a tool developed for the recovery of energy from organic wastes. A rational cell construction needs the fabrication of photoelectrodes, the design of a photoanode and a photocathode chamber, in addition to an ion-transport membrane for pollution treatment and electricity generation. In this review, comprehensive fundamental assessments and recent developments in the design of photocatalytic fuel cells, their applications, future prospects, and challenges are covered.